The Influence Of Work Ethics And Communication On Employee Work Achievement (Study at the Department of the Environment) - Maria Magdalena Minarsih; Tiara Nove Ria (SEAN Institute, 2022)
The purpose of this study was to determine the effect of work ethic on work performance, the effect of work communication on work performance and the simultaneous effect of work ethic and work communication on work performance in the Ministry of Environment. All employees of the environmental service are designated as defendants. Due to the primary data type, the data was collected using a questionnaire, which was then processed using the IBM SPPS Statistics software. The results of the regression test show that the work ethic variable partially has a positive and significant effect on work performance. The work communication variable also has a positive and significant effect on work performance. Demonstrating work ethic and work communication simultaneously have a positive and significant effect on work performance.